Evaluasi Penggunaan Obat Antihipertensi pada Pasien Rawat Jalan GGK dengan Hemodialisa di RSUP dr. Soeradji Tirtonegoro Klaten Tahun 2017 - Farah Afifah; Surya Amal (University Of Darussalam Gontor, 2019)
Hypertension is one of the major risk factors for chronic renal failure because it can cause damage to blood vessels in the kidney, thus reducing the ability of the kidneys to filter blood properly. Giving and analyzing antihypertensive drugs are very important in these circumstances, as it can accelerate the progression of the disease and increase the patient's mortality rate. Rasulullah sallallaahu 'alaihi wasallam, said: „There is a cure for every disease‟. If the medicine is right for an illness, it will be healed with the permission of Allah 'Azza wajalla